POLITIEKE INLICHTINGEN DIENST (PID) PADA MASA PEMERINTAH HINDIA BELANDA TAHUN 1916-1942 - Kurniawati, Atik Fajar; Yuniyanto, Tri; Bachri, Saiful (Candi, 2015)
The aims of this research are to identify: (1) the Politieke Inlichtingen Dienst history in Hindia-Belanda; (2) the role of Politieke Inlichtingen Dienst in taking care of political stability of Hindia-Belanda government; (3) the forming impact of Politieke Inlichtingen Dienst to the national movement in Hindia-Belanda.This study employed a historical history. The procedure of historical method included heuristic, critical, interpretation, and historiography. Technique of collecting data used was library study. The data source employed in this research was written source. In line with its type, the technique of analyzing data used in this research was historical analysis one.Based on the result of the research, it can be concluded that: (1) Forming of PID was influenced by two factors, there are intern dan ekstern factor. On May 6th, 1916, PID was formed by former Common Captain Staff of KNIL, W. Muurling. PID was formed to perceive and observe the possibility of the overseas threat and revolutionary activity in the country; (2) PID has responsibility to collect all information concerning any movement that happened in society. Based on the report which is gotten from PID, Governmental of Colonial can take the correct decision to be applied; (3) Forming impact of PID in Hindia-belanda that is the happening of "Crisis Movement".